Methodological report of a cross-sectional survey of abortion-related knowledge, attitudes and practices amongst health professionals in Britain, strategies adopted and lessons learned: evidence from the SACHA Study - R. S. French; M. J. Palmer; O. McCarthy; N. Salaria; R. Meiksin; J. Shawe; M. Lewandowska; R. Scott; K. Wellings; the SACHA Study Team (BMC Health Services Research)
Abstract Background Most surveys examining health professionals’ knowledge, attitudes and practices around abortion have used convenience samples and have targeted doctors. Our goal in the SACHA Study, drawing on evidence-based strategies to maximise response rates, was to achieve a representative sample of a wider range of health professionals, working in general practice, maternity services, pharmacies, sexual and reproductive health (SRH) clinics and specialist abortion services in Britain, to explore the knowledge, attitudes and experience of abortion care and views on future models of delivery. Methods A cross-sectional questionnaire-based survey of midwives, doctors, nurses and pharmacists in England, Scotland and Wales was undertaken between November, 2021 and July, 2022. We used a stratified cluster sampling approach to select a random sample of sites and all eligible staff within those services were asked to respond to the survey. Evidence-based strategies to maximise completion rates were adopted, including postal delivery of the one-page questionnaire with personal letter of invitation and a stamped address envelope for return, inclusion of an unconditional voucher and follow-up. Results Overall, 147 of the 314 (46.8%) health service sites randomly selected took part in the survey. Reasons for non-participation included local Research and Development (R&D) Department non-response, lack of resources or insufficient time to support or approve the study, lack of interest in or perceived relevance of the topic and insufficient capacity to take part, exacerbated by work demands during the COVID epidemic. Of the 1370 questionnaires sent to eligible identified participants within these services, 771 were completed and returned (56.3%). At the service level the highest proportion of returns was from SRH clinics (81.0%) and the lowest from general practice (32.4%). In relation to profession, returns were highest amongst midwives (69.6%) and lowest amongst pharmacists (36.5%). Conclusions Obtaining information about health professional knowledge, attitudes and practices is key to guide service development and policy and to identify gaps in training and service provision in abortion. Despite our attempts to gain a representative sample of health professionals, the challenges we experienced limited the representativeness of the sample, despite the use of an evidence-based strategy.